2009
DOI: 10.1109/tit.2009.2027527
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Measures of Sparsity

Abstract: Sparsity of representations of signals has been shown to be a key concept of fundamental importance in fields such as blind source separation, compression, sampling and signal analysis. The aim of this paper is to compare several commonlyused sparsity measures based on intuitive attributes. Intuitively, a sparse representation is one in which a small number of coefficients contain a large proportion of the energy. In this paper six properties are discussed: (Robin Hood, Scaling, Rising Tide, Cloning, Bill Gate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
199
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 595 publications
(202 citation statements)
references
References 49 publications
1
199
0
2
Order By: Relevance
“…Sparseness reflects the proportion of a neural population that is active in response to a stimulus. We used the Gini index (Hurley and Rickard, 2009) as a measure of sparseness: if only one neuron in a population responds to a given stimulus, the Gini index is 1, whereas if all neurons respond at the same level (compared with their maximal response), the Gini index is 0. We found that the sparseness of both identity and viewpoint representations (obtained by averaging single image responses across viewpoints and identities, respectively, before computing the Gini index) increases significantly from ML-MF to AM (one-way ANOVA: viewpoint, F (2,21) ϭ 199.4, p ϭ 2 ϫ 10 Ϫ14 ; identity, F (2,72) ϭ 3477.39, p ϭ 2 ϫ 10 Ϫ72 ; Fig.…”
Section: Neural Population Representations Of Viewpoint and Identity:mentioning
confidence: 99%
See 1 more Smart Citation
“…Sparseness reflects the proportion of a neural population that is active in response to a stimulus. We used the Gini index (Hurley and Rickard, 2009) as a measure of sparseness: if only one neuron in a population responds to a given stimulus, the Gini index is 1, whereas if all neurons respond at the same level (compared with their maximal response), the Gini index is 0. We found that the sparseness of both identity and viewpoint representations (obtained by averaging single image responses across viewpoints and identities, respectively, before computing the Gini index) increases significantly from ML-MF to AM (one-way ANOVA: viewpoint, F (2,21) ϭ 199.4, p ϭ 2 ϫ 10 Ϫ14 ; identity, F (2,72) ϭ 3477.39, p ϭ 2 ϫ 10 Ϫ72 ; Fig.…”
Section: Neural Population Representations Of Viewpoint and Identity:mentioning
confidence: 99%
“…Sparseness. We computed the Gini index (Hurley and Rickard, 2009) on the basis of the normalized average responses to each identity (and to each viewpoint) in the face views set for all neurons in a given patch. The normalized responses represent how strongly each neuron responds to each identity (or viewpoint) as a fraction of their maximal response (in the image set); the response is sparse if a given stimulus evokes a maximal response in only a few neurons.…”
Section: Introductionmentioning
confidence: 99%
“…By this a particular increase or decrease in sparsity is ensured with this measurements. The most commonly used and studied sparsity measures are the no rmlike measures [9] The measure simp ly calculates the number of non-zero coefficients…”
Section: ) Simulation Results and Discussionmentioning
confidence: 99%
“…The authors [4] examine and compare quantitatively several sparsity measures, and their findings show that the Gini index (GI) is the only measure that has all the defined properties. Hence, for the GI; given a vector x = [x 1 , ..., x N ], with its elements re-ordered from smallest to largest,…”
Section: Designing Adaptive Measurement Matrixmentioning
confidence: 99%
“…Although many natural signals of interest (i.e., smooth and piecewise smooth 1-D and 2-D signals with bounded variations) are not exactly sparse, norm |.| 0 may not be the desired measure of sparsity. Therefore, we derive an appropriate sparsity measure which utilizes the efficient GINI index (GI) introduced in [4].…”
Section: Introductionmentioning
confidence: 99%